Microsoft Office Training for Village Officials to Improve Computer Skills - Ade Risna Sari; Dedy Suryadi; Rulam Ahmadi; Ekbal Santoso; Eko Meiningsih Susilowati (BADAN PENERBIT STIEPARI PRESS, 2023)
A community service project called